Avaliação clínica do avanço da tuberosidade da tíbia, associada ou não a liberação do corno caudal do menisco medial em cães - Sousa, Diogo Garnica de (2011)
Several techniques have been described for stabilization of the stifle joint in dogs, and most recently corrective osteotomies have been recommended. Tibial tuberosity advancement (TTA) is a new technique for cruciate-deficient stifle in dogs and has been described in the veterinary literature. Thirty dogs with cranial cruciate ligament rupture undergoing TTA were studied. Dogs were grouped according to the presence of meniscal lesion at time of surgery: GI – intact medial meniscus, GII – intact medial meniscus undergoing meniscal release and GIII – meniscal lesion undergoing caudal pole hemimeniscectomy. Data regarding age, body weight, sex, lameness (LAM), tibial compression test (TCT), thigh girth, maximal extension and flexion, passive range of motiom (PROM) and internal tibial rotation were evaluated preoperatively and at days 10, 30, 60 and 360 post-surgery. Groups were identical preoperatively, except for PROM that differed significantly between GIII and the other groups. LAM decreased significantly 30 days after surgery, whereas TCT was significantly decreased at day 10 posto-op in all three groups evaluated.